The effects of conventional and unconventional monetary policy: Identification through the yield curve - Tomi Kortela; Jaakko Nelimarkka (Bank of Finland, 2020)
Since the Great Recession, the main evolution in monetary policy has been its attempts to affect the medium and the long-term interest rates with instruments other than the policy rate. Consequently, measuring the stance of monetary policy by a single interest rate becomes problematic. This study explores the macroeconomic effects of conventional and unconventional policy measures in the euro area in a unified framework. We identify simultaneously three monetary policy shocks that influence different parts of the yield curve. These shocks reflect various aspects of actions and communications of the European Central Bank in conventional and unconventional monetary policy periods. According to the results, conventional interest rate policy, forward guidance and quantitative easing have asymmetric output and price responses.
URN:NBN:fi:bof-202001221031
Keywords: C32; C36; E43; E52; C54; 330; Unconventional monetary policy; structural VAR; zero lower bound; term structureof interest rates